Chemistry and pharmacology of naturally occurring bioactive compounds - Brahmachari, Goutam (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
'Natural products play crucial roles in modern drug development and constitute a prolific source of novel lead compounds or pharmacophores for ongoing drug discovery programs. Chemistry and Pharmacology of Naturally Occurring Bioactive Compounds presents cutting-edge research in the chemistry of bioactive natural products and demonstrates how natural product research continues to make significant contributions in the discovery and development of new medicinal entities.'--Page [4] of cover.
Includes bibliographical references and index.
Keywords: Biological Products -- chemistry; Biological Products -- pharmacology; Drug Discovery; Produits naturels; Bioactive compounds; Bioorganic chemistry; Natural products